Is there a right to architecture? - Fisher, Thomas (Journal of Architecture and Urbanism, 2014)
Architecture, defined here most broadly as human shelter, addresses basic human needs of safety, security, privacy, and protection from the elements, but it is often viewed not as a right that every person has, but as a vehicle for controlling people, stimulating investment, and a range of other social, political, and economic interests. This article looks at the ethics of this situation from various ethical perspectives and concludes that, regardless of one’s point of view, every human being has a right to shelter.